(untitled) (Journal of the Management Sciences, 2024)
The study investigated organizational friendship and work passion in broadcasting corporation Bayelsa State, Nigeria. The researcher recognized three measures of organizational friendship and two indicators of work passion. Three fundamental objectives were designed namely to: examine the relationship between informational peer and harmonious passion in the broadcasting corporation Bayelsa State, Nigeria, investigate the relationship between collegial peer and obsessive passion in the broadcasting corporation Bayelsa State, Nigeria, and determine the relationship between special peer and harmonious passion in the broadcasting corporation Bayelsa State, Nigeria. Indeed, three research questions and three hypotheses were developed for the study. The researcher employed a survey design and the accessible population of the study comprised of 172 selected employees carefully chosen from six broadcasting corporations in Bayelsa State, Nigeria. A random sampling method was applied and the sample size was 120 employees selected through Taro Yamane’s formula. Instrument for data collection was harnessed through primary and secondary sources. Absence of workplace friendship has made most employees to see their jobs as boring and stressful which affect innovations in management of radio stations. Spearman’s rank correlation coefficient was used for the data analysis. The findings specified that organizational friendship has a positive effect on work passion. The researcher concluded that organizational friendship determines employees work passion. It was recommended that organizations should provide work- related information to enhance employee work passion and performance.